Numerical modeling of steel fillet welded joint. (March 2018) - Krejsa, Martin; Brozovsky, Jiri; Mikolasek, David; Parenica, Premysl; Flodr, Jakub; Materna, Alois; Halama, Radim; Kozak, Jaroslav
Highlights: The paper deals with the physical test of steel supporting elements, whose main purpose is obtaining of material, geometry and strength characteristics of the fillet welds. The main aims were designing and defining of tested samples for numerical modeling based on FEM analysis and using the commercial software ANSYS. Presented approach represents efficient computation of strain analysis of steel supporting elements using experimental obtained data. It was pointed out the possibilities of more detailed analysis of stresses and deformations in welds samples using a strain-gauge and a Q100 laser device for measuring the 3D deformation and infrared thermographic non-destructive testing. The described method of numerical modelling shows good agreement with behaviour of steel fillet welded joints during experiments. Abstract: The paper is focused on the numerical modeling of steel bearing elements and their verification using experiment. Currently, for the stress-strain analysis of the elements supporting structures it is possible to use many commercial software systems, based on the finite element method - FEM. It is important to to check and compare the results of FEM analysis with the results of physical verification test, in which the real behavior of the bearing element can be observed. The results of the comparison can be used for calibration of the computational model.The article deals with the physical test of steel supporting elements, whose main purpose is obtaining of material, geometry and strength characteristics of the fillet welds. The main aim was defining of tested samples numerical models for using FEM analysis and for the commercial software ANSYS. The pressure test was performed during the experiment, wherein the total load value and the corresponding deformation of the specimens under the load was monitored. The measurements were carried out for a more detailed analysis of stresses and deformations in welds samples using a strain-gauge and a Q100 laser device for measuring the 3D deformation and infrared thermographic non-destructive testing.Obtained data were used for the calibration of numerical models of test samples and they are necessary for further strain analysis of steel supporting elements.